Identification of Circulating MicroRNAs in Biliary Atresia by Next-Generation Sequencing. Issue 5 (November 2016) - Peng, Xiaofang; Yang, Liyuan; Liu, Haiying; Pang, Shuyin; Chen, Yihao; Fu, Jie; Chen, Yi; Wen, Zhe; Zhang, Ruizhong; Zhu, Bing; Yu, Jiakang; Invernizzi, Pietro
ABSTRACT: Objectives: Biliary atresia (BA) is an idiopathic neonatal liver disease, characterized by inflammatory and fibrotic obliteration of extrahepatic bile ducts. Therefore, reliable methods for noninvasive diagnosis are needed. The present study aimed to analyze circulating microRNAs (miRNAs) in patients with BA using next-generation sequencing for identifying novel diagnostic biomarkers. Methods: An initial screening of miRNAs in plasma from patients with BA and healthy controls (HCs) was performed on an Illumina next-generation sequencing platform. Differential miRNAs were validated by quantitative real-time polymerase chain reaction (qPCR). Target genes and related signal transduction pathways of differential miRNAs were predicted by online software. Results: In total, 146 differential miRNAs were identified by deep sequencing. Fifteen miRNAs with read counts >1000, that included 7 upregulated and 8 downregulated miRNAs, were predicted to be associated with liver fibrosis, biliary differentiation, and bile duct development. Of these, 6 miRNAs with read counts >5000 were analyzed by qPCR on an independent sample set comprising 44 patients with BA, 20 cholestatic disease controls, and 20 HCs. Two upregulated miRNAs (miR-122-5p, miR-100-5p) and 2 downregulated miRNAs (miR-140-3p, miR-126-3p) were confirmed by individual qPCR. Only miR-140-3p was significantly different from controls ( P < 0.05), yielding an area under receiver operating characteristic curve of 0.75 with sensitivity of 66.7% and specificity of 79.1% at optimal threshold. Conclusions: Our findings indicate that patients with BA exhibit a distinct profile of circulating miRNAs and that plasma miR-140-3p may be a promising diagnostic biomarker for this disease.